2012
DOI: 10.1097/inf.0b013e318247f533
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Children With Visceral Leishmaniasis

Abstract: AKI is a frequent complication in children with VL. The risk factors for AKI were secondary infections, high serum globulin and low serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 1 publication
2
24
0
1
Order By: Relevance
“…The main difference is a lower cutoff SCr to achieve the F category, requiring a GFR lower than 35 mL/min instead of a SCr of 4.0 mg/dL. Several studies have also validated pRIFLE in children, mainly in critically ill patients or after cardiac surgery [1116]. After that, it was mathematically demonstrated that it is not necessary to calculate the GFR and that, by using only the SCr increment, it was possible to diagnose and to assess AKI severity [17].…”
Section: Acute Kidney Injury Definitionmentioning
confidence: 99%
“…The main difference is a lower cutoff SCr to achieve the F category, requiring a GFR lower than 35 mL/min instead of a SCr of 4.0 mg/dL. Several studies have also validated pRIFLE in children, mainly in critically ill patients or after cardiac surgery [1116]. After that, it was mathematically demonstrated that it is not necessary to calculate the GFR and that, by using only the SCr increment, it was possible to diagnose and to assess AKI severity [17].…”
Section: Acute Kidney Injury Definitionmentioning
confidence: 99%
“…In Brazil, VL is endemic with 3298 cases in 2015, being responsible for 272 deaths, with a lethality rate of almost 8% . VL‐associated nephropathy has been related with higher mortality in these patients .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, VLassociated kidney disease is progressive and, without therapy, can result in end-stage renal disease (ESRD; approximately 1.5% of human cases). 4 Previous reports regarding the pathophysiology of VL-associated renal disease are conflicting, showing either presence or absence of IgG Q16 and complement protein C3. 1,7 Accurate assessment of VL-associated glomerular lesions early in their progression is essential to determining an efficacious treatment regimen and aid in determining prognosis.…”
Section: Q15mentioning
confidence: 99%